Predictive value of peripheral blood immune markers for castration-resistant prostate cancer development after endocrine therapy - Li, Fengshan; Cui, Luwei; Zhang, Guanlan; Hao, Jianwei (Frontiers in Oncology, 2026)
ObjectiveTo evaluate the predictive value of peripheral blood immune markers for progression to castration-resistant prostate cancer (CRPC) in prostate cancer (PCa) patients undergoing endocrine therapy.MethodsThis retrospective study included 106 PCa patients treated with endocrine therapy between 2021 and 2024. Peripheral blood immune parameters were compared between patients who did and did not experience progression to CRPC (progression and stable groups, respectively). The identified independent predictors of CRPC were then used to construct a nomogram for the identification of high-risk patients for early intervention. Internal validation was performed using the bootstrap method with 1000 resamples. Nomogram performance was evaluated by receiver operating characteristic curve, calibration curve, and decision curve analyses.ResultsUnivariate analysis showed significant differences (P < 0.05) in prostate-specific antigen level, Gleason score, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio, systemic immune inflammation index (SII), and pan-immune inflammation value (PIV), CD4+/CD8+ T cell ratio, and T4 stage between the progression and stable groups. Multivariate analysis further identified the PLR, SII, CD4+/CD8+ T cell ratio, and T4 stage as independent risk factors for CRPC development. The developed predictive model demonstrated strong predictive performance (area under the curve =0.934, Hosmer–Lemeshow P>0.05). The c-index for internal validation was 0.914, further confirming the predictive performance of the model. Employing clinically optimized thresholds, survival analysis confirmed that a PLR ≥140, SII ≥520, and CD4+/CD8+ T cell ratio <1.6 could significantly predict the 2-year CRPC risk.ConclusionThe PLR, SII, CD4+/CD8+ T cell ratio, and T4 tumor stage are independent risk factors for CRPC progression within 2 years of endocrine therapy. The survival prediction model based on these factors offers good predictive efficacy.